Spanlastic-laden nanogel as a plausible platform for dermal delivery of bimatoprost with superior cutaneous deposition and hair regrowth efficiency in androgenic alopecia - Bjad K. Almutairy; El-Sayed Khafagy; Mohammed F. Aldawsari; Abdullah Alshetaili; Hadil Faris Alotaibi; Amr Selim Abu Lila (Elsevier, 2024)
Bimatoprost (BIM) is a prostaglandin F2α analogs originally approved for the treatment of glaucoma and ocular hypertension. Recent studies have highlighted its potential to boost hair growth. The objective of this investigation is to challenge the potential of spanlastics (SLs) as a surfactant-based vesicular system for promoting the cutaneous delivery of BIM for the management of alopecia. BIM-loaded spanlastics (BIM-SLs), composed of Span as the main vesicle component and Tween as the edge activator, were fabricated by ethanol injection method. The formulated BIM-SLs were optimized by 23 full factorial design. The optimized formula (F1) was characterized for entrapment efficiency, surface charge, vesicle size, and drug release after 12 h (Q12h). The optimized formula (F1) exhibited high drug entrapment efficiency (83.1 ± 2.1%), appropriate zeta potential (−19.9 ± 2.1 mV), Q12h of 71.3 ± 5.3%, and a vesicle size of 364.2 ± 15.8 nm, which favored their cutaneous accumulation. In addition, ex-vivo skin deposition studies revealed that entrapping BIM within spanlastic-based nanogel (BIM-SLG) augmented the dermal deposition of BIM, compared to naïve BIM gel. Furthermore, in vivo studies verified the efficacy of spanlastic vesicles to boost the cutaneous accumulation of BIM compared to naive BIM gel; the AUC0-12h of BIM-SLG was 888.05 ± 72.31 μg/mL.h, which was twice as high as that of naïve BIM gel (AUC0-12h 382.86 ± 41.12 μg/mL.h). Intriguingly, BIM-SLG outperforms both naïve BIM gel and commercial minoxidil formulations in stimulating hair regrowth in an androgenetic alopecia mouse model. Collectively, spanlastic vesicles might be a potential platform for promoting the dermal delivery of BIM in managing alopecia.